Predominance of carbapenem-resistant Pseudomonas aeruginosa isolates carrying blaIMP and blaVIM metallo-β-lactamases in a major hospital in Costa Rica - Toval Maldonado, Francisco (2015)
This study aimed to assess the molecular basis of the resistance to carbapenems in clinical isolates of Pseudomonas aeruginosa recovered from a tertiary-level health facility in San José, Costa Rica. A total of 198 non-duplicated isolates were evaluated for their susceptibility to β-lactams, aminoglycosides and fluoroquinolones. The production of metallo-β-lactamases (MBLs), the presence of MBL encoding genes (blaIMP, blaVIM and blaGIM-1) and the occurrence of these genes within class 1 integrons were investigated. In addition, an ERIC2 PCR fingerprinting method was used to elucidate the distribution of the detected MBL genes within the strain collection. Of the 198 isolates tested, 125 (63.1 %) were categorized as carbapenem-resistant. The majority (88.8 %) of the carbapemen-resistant isolates also showed resistance to ceftazidime, cefepime, aztreonam, ticarcillin/clavulanic acid, amikacin, gentamicin, tobramycin, ciprofloxacin and gatifloxacin. Among the carbapenem-resistant isolates, 102 (81.6 %) showed MBL activity. Strikingly, both blaIMP and blaVIM genes were simultaneously detected in most (94.1 %) of the 102 MBL producers. Five carbapenem-resistant MBL producers were positive only for blaIMP genes. Almost 70 % of the isolates examined harboured the intI1 gene, accompanied by the sul1 and qacEΔ1 genes in 136 (99 %) and 122 (89 %) isolates, respectively. The majority (94.4 %) of the carbapenem-resistant isolates carried the intI1 gene, in contrast to 26 % of the carbapenem-susceptible isolates. Ninety-three out of 96 (96.9 %) isolates carrying both blaIMP and blaVIM genes also harboured the intI1, sul1 and qacEΔ1 genes. Gene cassettes from carbapenem-susceptible and MBL-negative carbapenem-resistant isolates encoded aminoglycoside-resistance enzymes (aadA2, aadA4 and aadA6) as well as orfD and qacF genes. RAPD analysis distributed 126 of the isolates in 29 clusters. Eighty of the 90 blaIMP (+) blaVIM (+) isolates were sorted into 16 different clusters, suggesting that the blaIMP and blaVIM genes detected were located within a genetic element capable of lateral transfer. Carbapenem-resistant MBL-positive isolates were recovered from almost all hospital wards and were over-represented in samples obtained from the surgical emergency and intensive care therapy units. Remarkably, three carbapenem-resistant isolates, exhibiting MBL activity and carrying both blaIMP and blaVIM genes, were recovered from outpatients. Sequence analysis of both bla genes in various isolates revealed that they correspond to the alleles blaIMP-18 and blaVIM-2. To our knowledge, this is the first report of the combination of two metallo-β-lactamases encoded by the blaIMP-18 and blaVIM-2 genes in P. aeruginosa.